Strength Perception and Its Relationship With the Accuracy and Speed Of Floater Jump Serve In Youth Volleyball - Sabaa, Ahmed; Aisa, Mustafa (Journal of Physical Education, 2016)
The importance of the research lies in strength perception in serving becausethrough serving a team can gain a direct point. The problem of the research lies in the resultof our Iraqi volleyball team in the Arabic Championship held in Morocco 2015. The aim ofthe research is to identify the type of relationship between strength perception and servingperformance accuracy in youth national Volleyball league. In addition to that, the researchaimed at identifying the type of relationship between strength perceptions and servingperformance speed in youth national Volleyball league.The researchers used the descriptive method. The subjects were (9) youthvolleyball players from the national team. The researchers concluded that youth volleyballplayers lack strength perception with speed and accuracy needed for floater jump serveperformance. Finally the researchers recommended designing stregnt exercises, strengthperception and controlling players' strength. In addition to that the researchers recommendedpaying attention to accuracy and speed in volleyball because it is important in directing ballsto the correct place using correct speed.